2007
DOI: 10.1080/15563650701502600
|View full text |Cite
|
Sign up to set email alerts
|

Methanol poisoning in Tunisia: Report of 16 cases

Abstract: Methanol poisoning continues to be a public health problem in Tunisia in spite of the different legislative measures. We report a series of 16 cases of methanol poisoning admitted to our Intensive Care Unit between December 2003 and April 2004. The patients' median age was 21.5 years (range 16 to 53 years) with a median SAPS II of 14 (range 12 to 84) and an APACHE II of 8 (range 6 to 36). The median latent period was 9.5 hours (range 4 to 24 hours) with a delay to medical consultation of 36 hours (range 6 to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 17 publications
4
41
0
Order By: Relevance
“…The outcome was related to the degree of metabolic acidosis, serum methanol concentration, coma upon admission, and the patient’s ability to hyperventilate 21. Furthermore, in another case series of 16 patients22 in Tunisia, a total of three (19%) patients who required mechanical ventilation because of deep coma or shock died within 6 hours. In a study by Verhelst et al,31 acute renal injury was found in 15 of the 25 (60%) patients.…”
Section: Discussionmentioning
confidence: 95%
“…The outcome was related to the degree of metabolic acidosis, serum methanol concentration, coma upon admission, and the patient’s ability to hyperventilate 21. Furthermore, in another case series of 16 patients22 in Tunisia, a total of three (19%) patients who required mechanical ventilation because of deep coma or shock died within 6 hours. In a study by Verhelst et al,31 acute renal injury was found in 15 of the 25 (60%) patients.…”
Section: Discussionmentioning
confidence: 95%
“…Alcohol can be produced using many different agricultural resources, and its illegal distribution is often highly visible in MMCs (e.g. Libya , Oman , Turkey , Tunisia and Indonesia ). Illegal homemade alcohol is strong and inexpensive, but if not made correctly can cause methanol poisoning .…”
Section: Challenges Facing Mmcsmentioning
confidence: 99%
“…It is possible that a structural anatomic variation could provide one explanation for this discrepancy. We are aware of only one previous cursory mention of unilateral optic neuropathy from methanol poisoning [6] and present here, in more detail, this uncommon occurrence.…”
mentioning
confidence: 79%